From European to World War: Dynamics of ‘Totalization’ and ‘Globalization’ of the Warfare in September 1939 — December 1941 - I. E. Magadeev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Internal dynamics of the warfare and evolution of the general strategic situation in the period of WWII, limited by the German aggression against Poland, on the one hand, and the failure of ‘Barbarossa’ and the U.S. entry into the war, on the other hand, were not so straightforward, as it is sometimes presented in scholarly accounts. This paper underlines ambivalences, intrinsic to the international and strategic situation between September 1939 and December 1941, focusing on the two interdependent though not identical trends of ‘totalization’ and ‘globalization’ of the warfare. To operationalize these processes the author suggests 3 parameters for each of them. As for ‘totalization’, they are: the duration of the war (a short war versus a long war), the degree of economy militarization, the degree of violence and absence of limitation in the warfare. To describe ‘globalization’ of the war the criteria are as follows: the geographical scale, the number of participants and the relative role and place of neutral powers, and, finally, the degree of the ‘bipolarization’ in the form of the two opposing coalitions. This paper concludes that the picture of WWII during the period under research was not identical to its textbook image of the total and global military conflict. Though the elements of the ‘total war’ were evident even in the pre-war period and included the preparation of the powers for the long struggle, a partial militarization of the economies based on the ‘lessons’ of WWI, and the ideological and criminal aims of Nazism, these elements needed time to take their ‘final’ forms and could not be implemented on a click. Moreover, the unexpected successes of the German ‘blitzkriegs’, as it seemed at the epoch, could turn the war into a series of relatively short military campaigns which didn’t demand the ‘total mobilization’. The same dichotomy was evident in the ‘globalization’ of the warfare: though the war was not only European from the beginning, due to the participation of the British and French colonial empires, due to the extension of the warfare to the North and East Africa and the global nature of the naval warfare, there were significant barriers to its extension to the whole world. Some of the Great Powers — the USSR and the USA, first of all — were officially neutral, there were a lot of expectations of the compromise peace and nobody knew exactly the final composition of the opposing blocs.